Ultrafine Fe3N nanocrystals coupled with N doped 3D porous carbon networks induced atomically dispersed Fe for superior sodium ion storage. (30th August 2022) - Liang, Ming; Xie, Haonan; Liu, Enzuo; Shi, Chunsheng; He, Chunnian; Zhao, Naiqin
Abstract: For conversion type Li/Na-ion batteries anode materials, constructing the nanocomposite with enough interface interaction is of great importance for enhancing the electrochemical reaction kinetics and keeping the integrity of the electrode structure even after a long-term cycle at a high current density. In addition, the highly reversible conversion of discharge product also plays a vital role in prolonging the cycling life of conversion type anode materials for Li/Na-ion batteries. In this work, a composite of isolated ultrafine Fe3 N nanocrystals (<15 nm) strongly coupled with N doped 3D porous carbon networks (N-3DPCN) were successfully fabricated via salt template-assisted calcination strategy. Both experimental results and theoretical simulations have validated that the powerful interface interaction between ultrafine Fe3 N nanocrystals (<15 nm) and N-3DPCN is bound up with the N-doping in 3DPCN, and the atomically dispersed metal Fe in the N-3DPCN (SAFe-N@3DPCN) formed during the discharge process of Fe3 N can catalyze the reversible conversion of discharge product Na3 N. Benefited from these advantages, the as-constructed Fe3 N@N-3DPCN composite delivers excellent Li/Na ion storage performance. This work shed light on the composite design of conversion-type materials and carbon materials for applications in energy storage fields and beyond. Graphical abstract: Image 1 Highlights: An effective synthesis strategy to improve the complex preparation process of Fex N/C is proposed. The interface coupling effect could enhance the interface interaction between ultrafine Fe3 N nanocrystals and N-3DPCN. The repetitive charge-discharge of Fe3 N@N-3DPCN electrode could induce the in-situ formation of atomically dispersed Fe.